How adhesion/growth-regulatory galectins-1 and -3 attain cell specificity: case study defining their target on neuroblastoma cells (SK-N-MC) and marked affinity regulation by affecting microdomain organization of the membrane - Kopitz, Jürgen; Bergmann, Marion; Gabius, Hans-Joachim (IUBMB life, 2010)
Galectins are potent effectors with conspicuous cell-type-specific activity profile. Its occurrence poses the question on the nature of the underlying biochemical determinants, in human SK-N-MC neuroblastoma cells involved in negative growth regulation. Since increase of surface presentation of ganglioside GM1 and homodimeric galectin-1 precedes growth inhibition, a direct interaction is suggested. We thus examined cell binding depending on glucosylceramide synthesis. It was drastically reduced by N-butyldeoxynojirimycin and threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol, adding decisive evidence for the assumed galectin/ganglioside binding. Glycoproteins do not compensate ganglioside depletion which was verified by measuring lipid-bound sialic acid. Binding affinity is significantly lowered by disrupting microdomain integrity, also effective for the competitive inhibitor galectin-3. This was caused by cell treatment with either 2-hydroxypropyl-β-cyclodextrin or filipin III. In this cell system, target specificity and topology of ligand presentation act together to enable high-affinity binding. © 2010 IUBMB IUBMB Life, 62(8): 624-628, 2010.